2006
DOI: 10.1097/01.blo.0000229356.81749.11
|View full text |Cite
|
Sign up to set email alerts
|

The Chitranjan Ranawat Award: Long-term Survivorship and Failure Modes of 1000 Cemented Condylar Total Knee Arthroplasties

Abstract: We examined factors affecting survivorship, and reasons for reoperation and revision of a cemented modular condylar total knee arthroplasty (TKA). One thousand and eight consecutive primary cemented cruciate-retaining TKAs performed at one institution were studied. At the time of review, 411 patients (562 knees) had died, 43 patients (45 knees) had their knee components revised or removed, and 47 patients (62 knees) were lost to followup. Mean followup of living patients with their TKA components in situ (244 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
149
2
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(166 citation statements)
references
References 33 publications
7
149
2
8
Order By: Relevance
“…Likewise, our revision TKA findings differ from those of prior reports implicating aseptic etiologies, including polyethylene wear, prosthetic loosening, and instability as the primary mechanisms for failed TKA [16,36,37,41,51,52]. Other studies have reported that periprosthetic joint infection is a primary indication for revision TKA [14,56]. Population and other regional differences might exist that may explain differing results in international registry data.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Likewise, our revision TKA findings differ from those of prior reports implicating aseptic etiologies, including polyethylene wear, prosthetic loosening, and instability as the primary mechanisms for failed TKA [16,36,37,41,51,52]. Other studies have reported that periprosthetic joint infection is a primary indication for revision TKA [14,56]. Population and other regional differences might exist that may explain differing results in international registry data.…”
Section: Discussioncontrasting
confidence: 94%
“…These differences carry implications for guiding care and resource allocation. New approaches to capturing the diagnoses and procedures that physicians and hospitals code as part of the billing process, such as the those used by the Nationwide Inpatients Sample (NIS), allow for larger-scale evaluations of the epidemiology of revision total joint arthroplasties than previously could be performed [13,14,17,37,51,56]. Prior studies [7,8] have been done that investigated the revised coding scheme in a national sample [1] to more clearly identify the indications for revision, procedure frequencies, and degree of adoption of the new diagnosis and procedure codes.…”
Section: Introductionmentioning
confidence: 99%
“…Infection is the leading cause of revision after TKA and the third most common reason for revision THA in the Medicare population. PJI can occur any time after the surgery, and there is no "gold standard" for diagnosis (2)(3)(4)(5)(6)(7)(8). PJI has a huge financial impact on the healthcare system.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that 6.6% to 38% of RTKAs are attributable to prosthetic knee infections [5,11,23,24,31,41,43,55,58,76,95,96]. Although some [56,63] prefer it, a two-stage procedure for chronic prosthetic knee infection requires temporary cement spacers to preserve limb length and reduce soft tissue retraction.…”
Section: Introductionmentioning
confidence: 99%